Postplacental IUD Insertion Using Ring Forceps versus Push and Push Technique - Hary Tjahjanto; Rahmad Rizal (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To compare IUD-endometrium (ED) distance and the incident of malposition postplacental CuT-380A IUD insertion in vaginal delivery between ring forceps technique and push and push technique. Method: This study was a double-blind randomized control trial, performed in September 2014 until March 2015 at Dr. Kariadi Hospital. Ring forceps and push and push insertion technique groups consisted of 25 subjects in each group. Follow-up was performed at 1-2 weeks, 6-8 weeks and >12 weeks after insertion. Result: The mean of IUD-ED distance in push and push group was shorter (but not statistically significant) than ring forceps group. The IUD-ED distance was at 1-2-week follow-up 4.1 (2.2) vs. 4.9 (3.4) mm; p=0.208, at 6-8-week follow-up: 2.6 (1.8) vs. 3.2 (3.7) mm; p=0.452, and at > 12-week follow-up: 0.9 (0.8) vs. 1.0 (0.9) mm; p=0.427, respectively. Malposition was found in 1-2-week follow-up, but the IUD was changed to the normal position (sagital position in uterine fundus) at 6-8-week and >12-week follow-up. Up to 3 months of follow-up, there was no occurrence of perforation, expulsion or pregnancy in both groups. Most of subjects (56% in the ring forceps, 68% in push and push groups) did not feel painful during IUD insertion. Conclusion: Push and push insertion technique clinically tends to produce IUD-ED distance shorter than ring forceps technique. Both techniques are comfortable, safe and effective. [Indones J Obstet Gynecol 2016; 4-2: 78-87] Keywords: immediate postplacental IUD insertion technique, IUDendometrium distance, IUD malposition, push and push technique, ring forceps technique